2010
DOI: 10.1126/science.1183147
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Acetylation of Cellular Proteins Creates Specific Degradation Signals

Abstract: The retained N-terminal methionine (Met) residue of a nascent protein is often N-terminally acetylated (Nt-acetylated). Removal of N-terminal Met by Met-aminopeptidases frequently leads to Nt-acetylation of the resulting N-terminal Ala, Val, Ser, Thr and Cys residues. Although a majority of eukaryotic proteins, for example, more than 80% of human proteins, are cotranslationally Nt-acetylated, the function of this extensively studied modification is largely unknown. Here we found, using the yeast Saccharomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
719
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(756 citation statements)
references
References 29 publications
24
719
1
1
Order By: Relevance
“…FOXO3a protein can be degraded by AKTtriggered ubiquitination-proteasome pathway (Plas and Thompson, 2003) or by caspase-3-like proteases in hematopoietic cells (Charvet et al, 2003). Recently, it is shown that N-terminal acetylation of cellular proteins creates specific degradation signals targeted by ubiquitin-dependent proteasome pathway (Hwang et al, 2010). As the NAMPT inhibition reduces sirtuin deacetylase activity, it is possible that N-terminal acetylation of certain proteins may be increased for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO3a protein can be degraded by AKTtriggered ubiquitination-proteasome pathway (Plas and Thompson, 2003) or by caspase-3-like proteases in hematopoietic cells (Charvet et al, 2003). Recently, it is shown that N-terminal acetylation of cellular proteins creates specific degradation signals targeted by ubiquitin-dependent proteasome pathway (Hwang et al, 2010). As the NAMPT inhibition reduces sirtuin deacetylase activity, it is possible that N-terminal acetylation of certain proteins may be increased for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The biological significance of N-terminal acetylation is still unclear, because no global trend regarding the functional consequences of N-terminal acetylation emerges. For some proteins, N-terminal acetylation may act as a degradation signal (88), whereas for others N-terminal acetylation may protect from proteolytic degradation and subsequently increases their half-life (89). N-terminal acetylation was also shown to be involved in protein sorting and addressing to cellular organelles (90) or to membrane (91).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation may therefore indicate a general modification pathway for plastid proteins in the cytosol. N-acetylation serves as a degradation signal for the ubiquitin ligase-proteasome system in yeast, and it was proposed to be involved in protein folding quality control (Hwang et al, 2010). Support for a function of plastid precursor protein N-acetylation in vivo came from the characterization of a mutant for a cytoplasmic N-acetyltransferase.…”
Section: N-terminal Met Excision and Acetylation Of Plastid Precursormentioning
confidence: 99%